Corporate Credit Risk Premia. (27th January 2018) - Berndt, Antje; Douglas, Rohan; Duffie, Darrell; Ferguson, Mark
Abstract: We measure credit risk premia—prices for bearing corporate default risk in excess of expected default losses—using Markit CDS and Moody's Analytics EDF data. We find dramatic variation over time in credit risk premia, with peaks in 2002, during the global financial crisis of 2008–09, and in the second half of 2011. Even after normalizing these premia by expected default losses, median credit risk premia fluctuate over time by more than a factor of 10. Credit risk premia comove with macroeconomic indicators, even after controlling for variation in expected default losses, with higher premia per unit of expected loss during times of market-wide distress. Countercyclical variation of premia-to-expected-loss ratios is more pronounced for investment-grade issuers than for high-yield issuers.